Princípio da prevenção e o meio ambiente do trabalho dos portuários de Manaus - Costa, Rodrigo Machado Cabral Da (2019)
This paper aims to address the issues concerning the prevention of labor environmental risks to which dockworkers of Manaus are exposed. It is necessary to establish a conceptualization aspect of working environment, applying the principles of environmental law and the rules of hygiene, health and safety protection of the human being in the workplace. Based on deductive research, this work of the domestic and international analysis on the working environment, environmental doctrine and labor environment, the structural principles of environmental law, the concept and characteristics of the working environment, to achieve aspects the theoretical and practical applicability of prevention in the working environment, as well as the jurisprudence examination of the Brazilian Courts and specific study on the Public Port of Manaus. The conclusion, made the above-mentioned analysis, is that the prevention principle is little adopted by the organs of supervision and compliance with environmental and labor standards as well as by port operators, which allow and impose an employment practice which means it has extremely hostile, with exposure of port workers, regardless of the legal relationship to which they are subjected to harmful agents to your health. The incisive performance of public and private agencies through legal and administrative instruments made available by the Brazilian legal order must be a constant in the environment of manauaras ports, whose rates of accidents, diseases or risk exposures reach alarming numbers. Thus, it is to recognize the need for specific protection to protect the work environment of the dockworkers of Manaus city, with the effective application of the principle of prevention, so that to preserve the life and health of these workers.